Biomass-fuelled combined heat and power: integration in district heating and thermal-energy storage. Issue 1 (27th February 2021) - Rezaei, Masoud; Sameti, Mohammad; Nasiri, Fuzhan
Abstract: Conventional approaches towards energy-system modelling and operation are based upon the system design and performance optimization. In system-design optimization, the thermal or mechanical characteristics of the systems providing for the heat or electricity demands were derived separately without integration with the energy source and without interaction with demand, which results in low-efficiency energy performance. This paper presents a key review on the integration of biomass-powered combined heat and power (BCHP) systems in district-heating systems as well as coupling with thermal-energy storage. In BCHP design, the appropriate sizing of the associated components as part of the district-heating system is very important to provide the optimal dispatch strategy as well as minimized cost and environmental impact while it co-operates with thermal-energy storage. Future strategies for the feasibility, evaluation and integration of biomass-powered energy systems in the context of district systems are also studied. Abstract : Biomass-fired combined heat and power (BCHP) systems are reviewed, with emphasis on the combination of BCHPs with district heating systems, integration with thermal-energy storage for efficiency enhancement, and system optimization. Graphic Abstract: